Systematic Review of Safety and Efficacy of Second- and Third-Generation CD20-Targeting Biologics in Treating Immune-Mediated Disorders - Kaegi, Celine; Wuest, Benjamin; Crowley, Catherine; Boyman, Onur (Frontiers in Immunology, 2022)
Background: B cells can contribute to immune-mediated disorders. Targeting CD20 has proved to be efficacious in several B cell-mediated immunopathologies, as illustrated by the use of rituximab, the first anti-CD20 monoclonal antibody (mAb). Following rituximab, second- and third-generation anti-CD20 mAbs have been developed and tried in immune-mediated diseases, including obinutuzumab, ocrelizumab, ofatumumab, ublituximab, and veltuzumab. However, their safety and efficacy has not been systematically reviewed. Objective: To evaluate safety and efficacy of obinutuzumab, ocrelizumab, ofatumumab, ublituximab, and veltuzumab for the treatment of immune-mediated disorders compared to placebo, conventional treatment or other biologics. Methods: The PRISMA checklist guided the reporting of the data. We searched the PubMed database between 4 October 2016 and 22 July 2021 concentrating on immune-mediated disorders. Results: The literature search identified 2220 articles. After screening titles and abstracts against the inclusion and exclusion criteria and assessing full texts, 27 articles were finally included in a narrative synthesis. Conclusions: Obinutuzumab has shown promising results in a case series of patients with phospholipase A2 receptor-associated membranous nephropathy and mixed results in systemic lupus erythematosus. Ocrelizumab has been approved for the use in patients with relapsing-remitting multiple sclerosis and primary progressive multiple sclerosis. Ocrelizumab was also tested in patients with rheumatoid arthritis, demonstrating promising results, and in systemic lupus erythematosus, revealing mixed results; however, in these conditions, its use was associated with increased risk of serious infections. Ofatumumab received approval for treating patients with relapsing-remitting multiple sclerosis. Moreover, ofatumumab showed promising results in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis, rheumatoid arthritis, and systemic lupus erythematosus, as well as mixed results in phospholipase A2 receptor-associated membranous nephropathy. Ublituximab was assessed in relapsing-remitting multiple sclerosis and neuromyelitis optica spectrum disorder, with promising results, however, the included number of patients was too small to conclude. Veltuzumab was tested in patients with immune thrombocytopenia resulting in improved platelet counts.